Generalized Ginzburg-Landau approach to inhomogeneous phases in nonlocal chiral quark models - Carlomagno, Juan Pablo (2015)
We analyze the presence of inhomogeneous phases in the QCD phase diagram within the framework of nonlocal chiral quark models. We concentrate in particular in the positions of the tricritical (TCP) and Lifshitz (LP) points, which are studied in a general context using a generalized Ginzburg-Landau approach. We find that for all the phenomenologically acceptable model parametrizations considered the TCP is located at a higher temperature and a lower chemical potential in comparison with the LP. Consequently, these models seem to favor a scenario in which the onset of the first order transition between homogeneous phases is not covered by an inhomogeneous, energetically favored phase.